Why dance matters to figure skating - Porter, J. (The Professional Skater PS Magazine, 2018)
What are some new opportunities for figure skating education in collaboration with dance models in die US? American Ice Theatre has been on this quest since 1997. Learning pedagogy, dance science, choreography, dance history, music, and artchanged the perspecrive in not only what dance education we can bring to skating, but our model for teaching and performing skating in general. As an example of success, a new satellite of American lce Theatre-Utah began in 2013 directed by Giselle Gorder, Rachel Peterson, and Stephanie Chace Bass who wanted to grow their current company, Crimson lce, to include education and performance opportunities outside of hockey games. In 2.5 years they quadrupled their company, brought over 40 skaters out of "retirement", hosted over 25 workshops and spear-headed the first AIT "school" in Park City, Utah offering group instruction modeled after dance. In their words, AIT has been just what the Utah skating community needed to thrive.